Nonlinear and scenario-dependent responses of carbon-nitrogen coupling in Chinese dryland soils driven by nitrogen deposition - Chuanqi Wang; Bo Wang; Yuwei Li; Dandan Zhou; Xin Li; Yanan Yu; Nan Lyu; Xuexia Hu; Ke Zhao; Pingping Zhu; Qianqian Qin; Pu Li (Pedobiologia, 2026)

Multi-omics analysis of the rhizosphere effects and molecular mechanisms of Ageratum conyzoides linn. at different stages of Cd, Pb, and Zn co-stress - Yuexin Fu; Mouyixing Chen; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu; Shaohong You (Journal of Environmental Management, 2026)

Sand barrier microplastics alter plant–soil interactions in artificial sand-fixation areas by constraining plant nutrient utilization - Nan Lu; Bo Wang; Yuwei Li; Dandan Zhou; Yanan Yu; Xin Li; Chuanqi Wang; Pingping Zhu; Qianqian Qin; Ke Zhao; Xuexia Hu; Pu Li (Journal of Arid Environments, 2026)

Machine learning for lithology identification in electrical image logging: A case study of the Chang 73 Sub-Member, Yanchang Formation, East Gansu region, Ordos Basin - Jiaqi Li; Hongping Bao; Shilong Liu; Pingping Shi; Feiming Gao; Liubin Wei; Langlang Wang; Hongyan Yu (Earth Science Informatics, 2026)

Sediment-associated Rare Earth Elements in an Urban River: Bioavailability and Ecological Risks to Aquatic Biota - Ruijie Peng; Pingping Wu; Zhilin Chen; Junzhuo Cai; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Processes, 2026)

Vegetation in Central Asia is more sensitive to soil moisture stress than to precipitation and vapor pressure deficit stresses - Hongwu Liang; Guli Jiapaer; Cun Chang; Tao Yu; Liancheng Zhang; Pingping Feng; Kaixiong Lin; Tongwei Ju; Xiapeng Jiang; Philippe De Maeyer; Tim Van de Voorde (Agricultural and Forest Meteorology, 2026)

Insight into the synergistic effects between pine sawdust and polyethylene during co-pyrolysis - Yu Yang; Pingping Tang; Xingyu Wang; Huiyan Duan; Junyu Xia (Process Safety and Environmental Protection, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

PRRSV nucleocapsid and nonstructural proteins dual-regulate CD40 expression via ATF-2 and AP-1 pathways - Chaolun Fu; Hongyan Gao; Yingchao Li; Chang Liu; Yuzhong Zhao; Youbo Li; Zhong Liu; Man Lu; Yang Shen; Yajing Xing; Yu Wang; Xiaotong Wu; et al. (Veterinary Microbiology, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Integrating machine learning with NSGA-Ⅱ to assess the synchronization effects of stormwater disaster hazard and green–blue infrastructure - Jiaxuan Chen; Sisi Wang; Pingping Luo; Chong-Yu Xu; Hongyu Zhao (Journal of Hydrology, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Linking runoff and sediment characteristics to karst development degree in small watershed - Zhengyi Tang; Rui Li; Li Qin; Tao Song; Benjin Yu; Pingping Yang; Jun Jing; Linlv Xiao (CATENA, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

Extreme climate indices in mountain settlements based on a hierarchical urban–rural classification approach in Qinba, China - Kanhua Yu; Wenting Yang; Juan Xu; Pingping Luo; Xuhui Wang; Zhaoyi Li (Urban Climate, 2025)

Oligopeptide-loaded metal-organic framework nanocomposites promote regulatory T cell differentiation against periodontitis - Yu Wang; Xiaoqian Gong; Hongli Chen; Pingping Niu; Zhiduo Liu; Yao Sun (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Prognostic biomarker MICAL2 and associates with proliferation, migration and immune infiltration in pancreatic adenocarcinoma - Huachao Yang; Pingping Yu; Jianping Gong (Journal of Applied Genetics, 2025)

Integrative Single-Cell Analysis Decodes Gene Expression and Chromatin Accessibility in the Developing Human Fetal Brain - Tiantian Xu; Huihui Tao; Lingling Zhou; Haiyan Yu; Shi Bai; Hui Guo; Zhipeng Zeng; Wei Shi; Chunmei Wen; Mengyao Wu; Xuejia Zheng; Pingping Ye; et al. (Molecular Neurobiology, 2025)

Spatial metabolomics reveals the effects of Acanthopanax senticosus on region-specific alterations in neurotransmitters and metabolites levels in the brains of α-syn transgenic Parkinson’s disease model mice - Qi Zheng; Yi Lu; Donghua Yu; Liangyou Zhao; Yu Wang; Pingping Chen; Fang Lu; Shumin Liu (Metabolic Brain Disease, 2025)

Characterization of Cyhalofop-butyl metabolism and identification of resistance genes in Barnyardgrass (Echinochloa crus-galli (L.) P. Beauv.) - Penglei Sun; Liangliang Niu; Xianmin Lan; Pingping Chen; Haiyan Yu; Jingchao Chen; Hailan Cui; Xiangju Li (Pesticide Biochemistry and Physiology, 2025)

Optimizing fertilization enhances sustainable vegetable production: combining on-farm composting and biochar application to improve vegetable yield, soil health, and socio-economic benefits - Bihui Tang; Pingping Ye; Xu Luo; Xinyi Yang; Tao Liang; Anle Chen; Duan Yu; Xiaozhong Wang; Ran Xiao (Journal of Cleaner Production, 2025)

Single cell transcription revealing key transcription factors in embryonic kidney development - Jingxian Huang; Bing Yan; Hongwei Wu; Hougang Yang; Shaodong Luan; Haiyan Yu; Wei Shi; Pingping Ye; Fang Yuan; Qiang Yan; Fanna Liu; Lianghong Yin; et al. (Molecular and Cellular Biochemistry, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

N6-methyladenosine reader YTHDF3-mediated CEBPA translation maintains genomic stability and stem cell function to prevent liver injury - Yaxu Liang; Weiwei Yu; Haifeng Sun; Dayu Wang; Zhibo Wang; Hailing Shi; Yang Cao; Zijie Zhang; Jun Liu; Zhongyu Zou; Jiangbo Wei; Tong Wu; et al. (Science China Life Sciences, 2025)

Ox-LDL Induces Neuron Apoptosis and Worsens Neurological Outcomes in aSAH via Fas/FADD Pathway - Yabin Song; Chen Yu; Dandan Bo; Junqi Sun; Yong Wang; Pingping Chen; Hanming Wu; Linghong Hong; Zhennan Ye; Long Zhang; Diangui Zhou (Molecular Neurobiology, 2025)

DHA Alleviates Excessive Copper-Induced Hepatocyte Injury by Inhibiting Pyroptosis via the ROS/NLRP3/NF-κB Pathway - Yufei Cao; Boran Zhou; Weiyin Zhang; Nan Mu; Pingping Zheng; Changhe Geng; Yu Wang (Biological Trace Element Research, 2025)

Temperature-dependent shell disease may relate to bacterial community changes of mud crab Scylla paramamosain in RAS - Kaijia Yu; Xiaopeng Wang; Chunlin Wang; Changkao Mu; Yangfang Ye; Pingping Zhan; Ronghua Li; Ce Shi (Aquaculture, 2025)

Enhanced stabilization and curcumin delivery by covalent NaCas-EGCG modified proso millet protein nanoparticles in Pickering emulsions - Yuting Fan; Jing Ren; Xinyi Li; Pingping Zhang; Yang Yao; Xiuzhu Yu; Shuang-kui Du (Food and Bioproducts Processing, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Metabolic engineering of Kluyveromyces marxianus to produce myo-inositol from starch - Qing Lan; Pingping Wu; Yao Yu; Jungang Zhou; Hong Lu (Bioresource Technology, 2025)

Life‐cycle greenhouse gas emissions associated with nuclear power generation in the United States - Jun Hong Clarence Ng; Pradeep Vyawahare; Pahola Thathiana Benavides; Yu Gan; Pingping Sun; Richard Boardman; Jason Marcinkoski; Amgad Elgowainy (Journal of Industrial Ecology, 2025)
Under the 2022 Inflation Reduction Act, tax credits of up to $3/kgH 2 are available to hydrogen producers if they generate emissions at levels below 0.45 kgCO 2 e/kgH 2 , spurring producers to explore how hydrogen production via electrolysis using electricity generated by nuclear power may qualify for such tax credits. With uranium as a primary fuel for nuclear power plants (NPPs) and no on‐site emissions, the upstream emissions associated with nuclear fuel supply chains largely determine the carbon intensity of nuclear energy. Using the GREET (Greenhouse gases, Regulated Emissions, and Energy use in Technologies) model, we evaluated the life‐cycle greenhouse gas (GHG) emissions of uranium production and the use of uranium to generate electricity in light water reactor (LWR) NPPs. We evaluated the process chemicals and energy inputs throughout the nuclear fuel supply chain to identify the major contributors to nuclear fuel cycle GHG emissions. Such emissions are estimated at 3.0 gCO 2 e/kWh at NPPs in the United States. The greatest share of nuclear fuel cycle GHG emissions—comprising 53% of total emissions—are associated with electricity consumption throughout the fuel supply chain. We extended the analysis to include an evaluation of the carbon intensity of H 2 production via electrolysis using nuclear power from LWRs. Finally, we examined the impact of future (2035 and 2050) electricity supply chain scenarios on nuclear fuel cycle GHG emissions. Our analysis revealed a decrease of 33% (2035) and 46% (2050) in the carbon intensity of nuclear electricity relative to current nuclear fuel cycle GHG emissions.

Human-induced N-P imbalances will aggravate GHG emissions from lakes and reservoirs under persisting eutrophication - Wei Yu; Fali Liu; Xianglan Jiao; Pingping Fan; Haiquan Yang; Yongmei Zhang; Jie Li; Jingan Chen; Xuede Li (Water Research, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

Identification of Dufulin photolysis and hydrolysis products in water using a 13C stable isotope assisted HPLC-HRMS strategy - Bochi Yu; Yanli Man; Gabriel Sigmund; Pingping Wang; Jun Xie; Wei Wang; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Xingang Liu (Water Research, 2025)

Trees show higher resilience than herbs under phosphorus deficit induced by 12‐year simulated acid rain - Guangcan Yu; Mianhai Zheng; Ying‐Ping Wang; Mengxiao Yu; Jun Jiang; Enqing Hou; Nannan Cao; Shu Ye; Songjia Chen; Jingtao Wu; Fengcai Liu; Linhua Wang; et al. (Ecology, 2025)
Acid rain, with 60% deposition in Asia, may exacerbate plant phosphorus (P) limitation; however, its long‐term effects on different plant life‐forms remain largely undetermined. Understanding these effects is essential for predicting ecosystem resilience and promoting forest health under environmental change. Herein, we investigated the P status in two tree and two herb species and their rhizosphere soils after 12 years of acid treatment at three pH levels (pH: 4.0, 3.5, and 3.0) in a tropical forest in Southern China. We found that leaf, litter, and root P; leaf N and P resorption efficiency; and their ratios remained stable in trees; however, herb leaf and litter P levels declined. Acid addition reduced inorganic P in tree rhizosphere soil and inorganic and organic P in herb rhizosphere soil. Rhizosphere soil P fractions were more regulated by soil physicochemical properties and less regulated by microbial community in trees than in herbs. Under long‐term simulated acid rain, stable tree P status benefited from soil inorganic P depletion, and herbs partially met their P requirements via biological mineralization of soil organic P. These distinct P‐associated responses and acquisition strategies provide insights into safeguarding forest health among plants of different functional types under long‐term acid rain events.

Food-derived peptides as novel therapeutic strategies for NLRP3 inflammasome-related diseases: a systematic review - Ziqi Zhang; Yuan Zhang; Meiying Zhang; Chenfeng Yu; Pingping Yang; Minxuan Xu; Jitao Ling; Yuting Wu; Zicheng Zhu; Yixuan Chen; Ao Shi; Xiao Liu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Boosting lactic acid photocatalytic synthesis from biomass sugars: The synergistic effect of N-doped carbon dots on ultrathin carbon nitride - Xiao Cao; Xin Wang; Yiyang He; Jixin Li; Haiyan Yang; Pingping Zhang; Songrui Yang; Haixiang Yu; Suyun Xu; Haiping Yuan; Lin Gu (Food Chemistry, 2025)

An efficient, robust, and affordable photothermal membrane using polyvinyl alcohol encapsulated MXene/non-woven fibers for solar desalination/sewage purification - Ye Cao; Pingping Gong; Peng Yu; Yijing Wang; Zhenli Zuo; Changyuan Pan; Xinbing Wang; Peng Zhong; Xiaohua Ma (Chemical Engineering Journal, 2025)

Treatment of sludge hydrothermal carbonization wastewater by ferrous/sodium percarbonate system: Effect of wastewater composition and role of coagulation and oxidation - Liming Liu; Luna Zhao; Shiyun Jin; Wei Zou; Hongxia Wang; Yu Xie; Changlan Hou; Yunbo Zhai; Pingping Luo (Water Research, 2024)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Satellite navigation signal quality monitoring algorithm based on DBO-SVM - Ershen Wang; Yilin He; Tengli Yu; Liang Liu; Song Xu; Pingping Qu; Tao Pang (Advances in Space Research, 2024)

Photobacterium pectinilyticum sp. nov., a novel bacterium isolated from surface seawater of Qingdao offshore - Yunqi Ding; Pingping Zhang; Yi Liu; Mei Liu; Yaru Wang; Ronghua Liu; Shuxian Yu; Xiao-Hua Zhang; Xiaolei Wang (Antonie van Leeuwenhoek, 2024)

Pioneer plants promote soil formation in a mixture of bauxite tailings and red mud - Xusheng Jiang; Mengting Lin; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu (Journal of Environmental Management, 2024)

Performance of loach to reduce clogging matter in vertical-flow constructed wetlands: Hydraulic evaluation and metabolic processes - Xiuzheng Fu; Fanlong Kong; Pingping Duan; Fanyi Li; Wenxuan Hu; Xiaomin Liu; Zhengda Yu; Yuqian Cui (Chemical Engineering Journal, 2024)

The effect of Ca2+-calcineurin signaling pathway on the antifungal activity of Pd-D-V against Botrytis cinerea - Yao Yu; Xinru Li; Yiping Hou; Min Wei; Yiyun Qian; Yuxin Zhou; Min Yin; Yanqin Jiang; Pingping Song (Pesticide Biochemistry and Physiology, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

Rotation of Celosia argentea and Sedum plumbizincicola promotes Cd phytoextraction efficiency - Jie Liu; Xusheng Jiang; Xuehong Zhang; Pingping Jiang; Guo Yu (Journal of Hazardous Materials, 2024)

Crystalline-topologies engineering of bio-spore-derived hard carbon for efficient low-potential potassium ion storage - Wenli Zhu; Pingping Lan; Taijin Tang; Cunhuai Yu; Pei Kang Shen; Zhi Qun Tian (Chemical Engineering Journal, 2024)

Association Between Circulating Zinc Levels and Risk Factors of Metabolic Syndrome: Insights from a Bi-directional Mendelian Randomization Analysis and Cross-Sectional Study - Yuanyuan Wu; Guoqiong Xu; Ruixue Bai; Pingping Yu; Zhongxiang He; Mengxue Chen; Yukun Hu; Tao Jiang; Yuanhang Yang; Dongfang Liu; Ying Mei; Xiaoya Qi; et al. (Biological Trace Element Research, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Effect of liquid nitrogen spray quick-freezing technology on the quality of bamboo shoots, Dendrocalamus brandisii from Yunnan Province, China - Zhenmei Fan; Hui Shen; Tenggen Hu; Lijuan Yu; Yujuan Xu; Jijun Wu; Pingping Shi; Xianliang Song; Yuanshan Yu (Journal of Food Engineering, 2024)

Effect of apple high-methoxyl pectin on heat-induced gelation of silver carp myofibrillar protein - Han Yu; Yunfeng Zhao; Runze Li; Xin Guo; Pingping Liu; Jian Zhang (Food Chemistry, 2024)

Enhancing methanol tolerance of Thermomyces lanuginosus lipase by rational design and biodiesel production through one-step feeding of methanol - Pingping Qu; Raudah Lazim; Dongdong Li; Rui Xu; Fei Wang; Xun Li; Yu Zhang (Journal of Cleaner Production, 2024)

The relationship between maternal exposure to ambient air pollutants and premature rupture of membranes: A systematic review and meta-analysis - Yaxin Liang; Min Li; Qiubo Lyu; Pingping Li; Yuhan Lyu; Yue Yu; Wuqiang Peng (Environmental Pollution, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Physiological and biochemical responses of Leersia hexandra Swartz to nickel stress: Insights into antioxidant defense mechanisms and metal detoxification strategies - Mouyixing Chen; Pingping Jiang; Xuehong Zhang; Geoffrey I. Sunahara; Jie Liu; Guo Yu (Journal of Hazardous Materials, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Chitosan/alginate dialdehyde trilayer films with cinnamaldehyde nanoemulsions for grass carp preservation - Junli Dong; Dawei Yu; Liming Zhang; Guohao Wang; Pingping Zhang; Yitian You; Yanshun Xu; Wenshui Xia (Food Hydrocolloids, 2024)

Full-scale upgrade activated sludge to continuous-flow aerobic granular sludge: Implementing microaerobic-aerobic configuration with internal separators - Cheng Yu; Kaijun Wang; Kaiyuan Zhang; Ruiyang Liu; Pingping Zheng (Water Research, 2024)

Response differences of gut microbiota in oligofructose and inulin are determined by the initial gut Bacteroides/Bifidobacterium ratios - Pingping Yin; Ting Du; Shanrong Yi; Chengcheng Zhang; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Research International, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Incorporation of ascorbic acid and L-cysteine in sodium carboxymethyl cellulose coating delays color deterioration and extends the shelf-life of fresh-cut asparagus lettuce (Lactuca sativa var. angustata) - Renying Yu; Huibo Song; Yanan Chen; Nan Shi; Hui Shen; Pingping Shi; Huosheng Shu; Xiaoxue Kong; Lijuan Yu; Haibo Luo (Postharvest Biology and Technology, 2023)

Novel TFC membrane with PMIA thin-film as active layer fabricated by the T-FLO technique for dye desalination - Pingping Li; Zhenliang Xu; Dibakar Pandaya; Yinxin Fang; Linglin Gao; Rui Ding; Kaiqi Yu (Journal of Environmental Chemical Engineering, 2023)

Realization of highly deformable freestanding borophene hybrid film for flexible energy storage device - Jiali Yu; Zhimin Fan; Fei Yu; Hang Zhao; Pingping Yao; Shengnan Chen; Haiyan Yang; Caizhen Zhu; Jian Xu (Chemical Engineering Journal, 2023)

Meta-analysis reveals different functional characteristics of human gut Bifidobacteria associated with habitual diet - Pingping Yin; Chengcheng Zhang; Ting Du; Shanrong Yi; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Research International, 2023)

Photocatalysis enhanced constructed wetlands effectively remove antibiotic resistance genes from domestic wastewater - Pingping Chen; Xiaofei Yu; Jingyao Zhang (Chemosphere, 2023)

Repeated Digestion by Earthworms on Tetracycline Degrading and Biological Responses in Tetracycline-Contaminated Sewage Sludge - Ping Liu; Taotao Zha; Si-Qi Xia; Pingping Sun; Yu-Feng Wu; Haitao Zhao; Ke Feng (Water, Air, & Soil Pollution, 2023)

Plant above-ground biomass and litter quality drive soil microbial metabolic limitations during vegetation restoration of subtropical forests - Shuo Zhang; Ying-Ping Wang; Xi Fang; Jinlei Chen; Nannan Cao; Pingping Xu; Mengxiao Yu; Xin Xiong; Xiangping Tan; Qi Deng; Junhua Yan (Soil Ecology Letters, 2023)

Prediction of zebrafish embryonic developmental toxicity by integrating omics with adverse outcome pathway - Xiao Gou; Cong Ma; Huimin Ji; Lu Yan; Pingping Wang; Zhihao Wang; Yishan Lin; Nivedita Chatterjee; Hongxia Yu; Xiaowei Zhang (Journal of Hazardous Materials, 2023)

Investigating the dielectric properties of lunar surface regolith fines using Mini-RF SAR data - Yao Gao; Yanan Dang; Pingping Lu; Wentao Hou; Fei Zhao; Bingnan Wang; Weidong Yu; Robert Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Integrated transcriptome and metabolome analysis reveals the mechanism of tolerance to manganese and cadmium toxicity in the Mn/Cd hyperaccumulator Celosia argentea Linn - Guo Yu; Habib Ullah; Xinshuai Wang; Jie Liu; Baoliang Chen; Pingping Jiang; Hua Lin; Geoffrey I. Sunahara; Shaohong You; Xuehong Zhang; Asfandyar Shahab (Journal of Hazardous Materials, 2023)

A global survey of organophosphate esters and their metabolites in milk: Occurrence and dietary intake via milk consumption - Shunying Yao; Zhixiong Shi; Pei Cao; Lei Zhang; Yu Tang; Pingping Zhou; Zhaoping Liu (Journal of Hazardous Materials, 2023)

K+ and CeO2 nanoparticles modified OMS-2 nanorods for enhanced activity and stability of photocatalytic toluene oxidation: K+ charge modulation and mechanistic investigation - Pingping Yu; Nan Li; Weixin Zou; Xiaoqian Wei; Jiawei Ji; Li Han; Yandi Cai; Wei Tan; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Application of an integrated loach-plant-substrate-microbes non-aerated saturated vertical flow constructed wetlands: Mechanisms of pollutants removal and greenhouse gases reduction - Xiuzheng Fu; Zhengda Yu; Fanlong Kong; Pingping Duan; Fanyi Li; Lingzhu Zhang; Zhongying Liu; Yuqian Cui (Bioresource Technology, 2023)

Expression of RUNX2/LAPTM5 in the Induction of MC3T3-e1 Mineralization and Its Possible Relationship with Autophagy - Lei Xing; Yanqin Li; Wenhao Li; Rong Liu; Yuanming Geng; Weiqun Ma; Yu Qiao; Jianwen Li; Yingtao Lv; Ying Fang; Pingping Xu (Tissue Engineering and Regenerative Medicine, 2022)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Breast Cancer Awareness Based on Health Information Literacy and Influential Factors among Female Nursing Students in China - Shu Yang; Ping Li; Lin Yu; Na Liu; Jie Wang; Pingping Guo; Xuehui Zhang; Wei Zhang (Journal of Cancer Education, 2022)

Pathways of cadmium fluxes in the root of the hyperaccumulator Celosia argentea Linn. - Pingping Jiang; Yingyi Zheng; Jie Liu; Guo Yu; Fanyu Lin (Environmental Science and Pollution Research, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Recent advances in construction and regulation of yeast cell factories - Xue Jiao; Yuehao Gu; Pingping Zhou; Hongwei Yu; Lidan Ye (World Journal of Microbiology and Biotechnology, 2022)

Serotonin 2A receptor function and depression-like behavior in rats model of hypothyroidism - Zhicheng Jin; Jianer Ling; Jing Yu; Mengzi He; Pingping Ni; Fang Zhang; Yizhen Wang (Experimental Brain Research, 2021)

Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

PD-1 expression is elevated in monocytes from hepatocellular carcinoma patients and contributes to CD8 T cell suppression - Jin Yun; Genhua Yu; Pingping Hu; Yang Chao; Xingyu Li; Xiaobo Chen; Qichun Wei; Junfeng Wang (Immunologic Research, 2020)

Prenatal diagnosis and neonatal phenotype of a de novo microdeletion of 17p11.2p12 associated with Smith‒Magenis syndrome and external genital defects - Pingping Zhang; Yanmei Sun; Haishen Tian; Limin Rong; Fangna Wang; Xiaoping Yu; Yali Li; Jian Gao (Journal of Genetics, 2020)

Mechano growth factor pretreatment yield mechanical stimuli induced cell stress responses in ligament fibroblasts of osteoarthritis via activating ATF-2 - Yu Ma; Yang Song; Linhao Li; Lili Dong; Chunli Wang; Pingping Wang; Li Yang (Biotechnology Letters, 2020)

Interaction of Mn and Cd during their uptake in Celosia argentea differs between hydroponic and soil systems - Jie Liu; Guo Yu; Pingping Jiang; Xingfeng Zhang; Dejia Meng; Zhe Chen; Alan J. M. Baker; Rongliang Qiu (Plant and Soil, 2020)

Decreased decidual epithelial sodium channel (ENaC) alpha and gamma subunits in recurrent pregnancy loss (RPL) - Tiantian Yu; Chun Feng; Pingping Lv; Gufeng Xu; Lihua Hong; Yimeng Xiong; Xiaoyan Guo; Tong Li; Jianzhong Sheng; Hefeng Huang; Xinmei Liu (Science China Life Sciences, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

Transcriptomic analysis reveals the effect of the exopolysaccharide of Psychrobacter sp. B-3 on gene expression in RAW264.7 macrophage cells - Pingping Zhang; Jiang Li; Leiye Yu; Jingfang Wei; Tong Xu; Guojie Sun (Acta Oceanologica Sinica, 2018)

Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae) - Zhen Ye; Juanjuan Yuan; Min Li; Jakob Damgaard; Pingping Chen; Chenguang Zheng; Haibin Yu; Siying Fu; Wenjun Bu (Journal of Biogeography, 2018)
Aim Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis , to explore the relative roles played by these two factors in population genetic connectivity. Location Sichuan Basin, China. Methods Mitochondrial ( COI , COII , Cytb, 16S) and nuclear ( EF ‐1α, ITS 1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum ( LGM ) to the present were predicted through fine‐tuned ecological niche modelling ( ENM ). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated using beast . Finally, the least cost path ( LCP ) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot ( BSP ) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis , in global biodiversity hotspots is proposed and discussed in this paper.

Formulation and In Vitro Release Kinetics of Mucoadhesive Blend Gels Containing Matrine for Buccal Administration - Xiaojin Chen; Jun Yan; Shuying Yu; Pingping Wang (AAPS PharmSciTech, 2018)

Vectorization of classified remote sensing raster data to establish topological relations among polygons - Bin Xu; Jianping Chen; Pingping Yu (Earth Science Informatics, 2017)

Increased Active Tumor Targeting by An αvβ3-Targeting and Cell-Penetrating Bifunctional Peptide-Mediated Dendrimer-Based Conjugate - Pengkai Ma; Huajun Yu; Xuemei Zhang; Hongjie Mu; Yongchao Chu; Ling Ni; Pingping Xing; Yiyun Wang; Kaoxiang Sun (Pharmaceutical Research, 2017)

Resveratrol Pretreatment Decreases Ischemic Injury and Improves Neurological Function Via Sonic Hedgehog Signaling After Stroke in Rats - Pingping Yu; Li Wang; Fanren Tang; Li Zeng; Luling Zhou; Xiaosong Song; Wei Jia; Jixiang Chen; Qin Yang (Molecular Neurobiology, 2017)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Crustal movement estimation based on an unchanged-feature points method using TerraSAR-X intensity images: application to the 2011 Tohoku earthquake - Kangning Du; Pingping Lu; Robert Wang; Yunkai Deng; Weidong Yu; Timo Balz (International Journal of Remote Sensing, 2014)

An Experimental Study of the Influence of Interfacial Tension on Water–Oil Two-Phase Relative Permeability - Pingping Shen; Bin Zhu; Xian-Bin Li; Yu-Shu Wu (Transport in Porous Media, 2010)